Influence of vitreoretinal traction localization on horseshoe tear configuration and risk of rhegmatogenous retinal detachment - A. V. Doga; L. A. Kryl,; M. R. Taevere (Офтальмохирургия, 2021)
Purpose. To evaluate the relationship between the shape of horseshoe tear and the localization of vitreoretinal tractions (VRT) using methods of the peripheral vitreoretinal interface visualization and classify horseshoe tears by shape for sur gical planning.Material and methods. We studied horseshoe tears parameters of 52 patients (52 eyes). The localization of VRT was determined by widefield OCT, the horseshoe tear shape was determined as the ratio of length to width of the tear (l/b) by multispectral laser scanning. The ratio of the obtained data was evaluated by the Spearman correlation analysis. We used Ward’s method of hierarchical clustering to classify the horseshoe tears by shape. The obtained data were used to perform YAG-laser excision of the vitreoretinal adhesion zone in patients with rhegmatogenous retinal detachment as part of the combined microinvasive laser-surgical technology.Results. The l/b ratio ranged from 1/4 to 3/1. A strong negative correlation has been revealed between the horseshoe tear shape and the fixation of vitreoretinal tractions (rs -0.95; p <0.05). Horseshoe tears were identified in 4 groups using Ward’s method of clustering. Each group corresponded to a specific localization of VRT. The extension of VRT beyond the tear was associated with a high risk of rhegmatogenous retinal detachment.Conclusion. A significant correlation has been found between the studied factors confirm the possibility of using data on the horseshoe tear shape for an approximate evaluation of vitreoretinal adhesion localization. The obtained data allows to determine the exact VRT excision zone when performing combined laser-surgical technology without the need for preoperative wide-field OCT.